The tax-rate induced bond substitution hypothesis and the traditional textbook treatment of the relationship between tax-free and taxable bond yields. Issue 14 (21st March 2020) - Cebula, Richard J.; Clark, J.R.
ABSTRACT: This empirical study posits and tests the 'tax-rate induced bond substitution hypothesis, ' wherein the propensity for bond buyers to substitute tax-exempt municipal bonds for taxable bonds in their portfolios is hypothesized to be an increasing function of the maximum federal personal income tax rate. This substitution acts to elevate the real interest rate yield on taxable bonds while diminishing it on tax-exempt bonds, ceteris paribus . Two measures of real interest rates are included in the present analysis, ex post real interest rate and ex ante real interest rate. Empirical estimations for the 1981–2018 period provide strong support for the hypothesis. They reveal that the real interest rate yield on high-grade tax-exempt municipal bonds is a decreasing function of the maximum marginal federal personal income tax, whereas the real interest rate yield on taxable ten-year Treasury notes is an increasing function of that same tax rate. We examine the implications of this study and the information underlying it for the traditional formulaic textbook treatment of the relationship between yields on bonds whose interest rate payments are taxable versus those whose interest rate payments are tax exempt and find it is not as dependable as the textbooks would have us believe.